Impact of Nursing Interventions on Physical Recovery of Disaster Victims: A Scoping Review - Wiguna, Yutika; Purwandi, Purwandi; Hartati, Tita; Satrio, Rizki Juniar Eko; Utami, Nisa; Sijabat, Pasuria Br; Indriati, Ririn; Trisyani, Yanny (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2025)
Disasters, whether natural or human-induced, frequently lead to significant physical injuries and complex health conditions among affected populations. In such contexts, nurses serve as frontline responders who deliver critical care aimed at promoting physical recovery and preventing further complications. This scoping review explores and synthesizes existing literature on the impact of nursing interventions on the physical recovery of disaster victims. The review was conducted in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. A systematic search was carried out in three major electronic databases PubMed, Scopus, and Web of Science targeting articles published between 2015 and 2025. The following Boolean search string was used: ((disasters) OR ("disaster victims") OR ("disaster survivors")) AND ((nurses) OR ("nursing intervention") OR ("nursing care")) AND (("physical recovery") OR ("wound healing") OR ("pain management") OR ("mobility improvement") OR ("quality of life")). Following the application of predefined inclusion and exclusion criteria, three studies were selected for the final synthesis. The findings reveal that nursing interventions such as wound care, pain management, infection control, physical rehabilitation, and health education play a vital role in enhancing the physical recovery of individuals affected by disasters. The success of these interventions is often shaped by factors including timeliness, cultural appropriateness, and interdisciplinary collaboration. In conclusion, this review underscores the essential contribution of nurses in disaster recovery efforts and highlights the need for continued development of evidence-based, culturally sensitive, and standardized nursing practices to optimize health outcomes in post-disaster settings.